An antipathogenic compound that targets the OxyR peroxide sensor in Pseudomonas aeruginosa. Issue 4 (8th April 2021) - Oh, Hyo-Young; Jalde, Shivakumar S.; Chung, In-Young; Yoo, Yeon-Ji; Jang, Hye-Jeong; Choi, Hyun-Kyung; Cho, You-Hee
Abstract : Introduction. Antipathogenic or antivirulence strategy is to target a virulence pathway that is dispensable for growth, in the hope to mitigate the selection for drug resistance. Hypothesis/Gap Statment. Peroxide stress responses are one of the conserved virulence pathways in bacterial pathogens and thus good targets for antipathogenic strategy. Aim. This study aims to identify a new chemical compound that targets OxyR, the peroxide sensor required for the full virulence of the opportunistic human pathogen, Pseudomonas aeruginosa . Methodology. Computer-based virtual screening under consideration of the 'eNTRy' rules and molecular docking were conducted on the reduced form of the OxyR regulatory domain (RD). Selected hits were validated by their ability to phenocopy the oxyR null mutant and modulate the redox cycle of OxyR. Results. We first isolated three robust chemical hits that inhibit OxyR without affecting prototrophic growth or viability. One (compound 1) of those affected the redox cycle of OxyR in response to H2 O2 treatment, in a way to impair its function. Compound 1 displayed selective antibacterial efficacy against P. aeruginosa in Drosophila infection model, without antibacterial activity against Staphylococcus aureus . Conclusion. These results suggest that compound 1 could be an antipathogenic hit inhibiting the P. aeruginosa OxyR. More importantly, our study provides an insight into the computer-based discovery of new-paradigm selective antibacterials to treat Gram-negative bacterial infections presumably with few concerns of drug resistance.